A network comparison on efficacy and safety profiling of PD-1/PD-L1 inhibitors in first-line treatment of advanced non-small cell lung cancer - Fu, Jie; Yan, Yi-Dan; Wan, Xu; Sun, Xiao-Fan; Ma, Xiu-Mei; Su, Ying-Jie (Frontiers in Pharmacology, 2025)
ObjectivePD-1/PD-L1 inhibitors are novel immunotherapeutic agents that have been approved for first-line treatment in advanced non-small cell lung cancer (NSCLC). This study aims to evaluate the efficacy and safety of PD-1/PD-L1 inhibitors, which have completed phase 3 clinical trials, as a first-line treatment in patients with advanced NSCLC.Materials and methodsA systematic search of PubMed, Embase and the Cochrane Library was performed to extract eligible literature up to October 2023. Findings included overall survival (OS), objective response rate (ORR), progression-free survival (PFS), and grade ≥3 treatment-related adverse events (TRAEs). Furthermore, subgroup analyses were conducted based on PD-L1 expression levels and histological type.ResultsWe analyzed 29 studies including 18,885 patients. In analyses of all patients, penpulimab plus chemotherapy led the way for OS (HR 0.55, 95% CI: 0.40–0.75) and PFS (HR 0.43, 95% CI: 0.27–0.67). Regarding OS, for patients with PD-L1 expression ≥50%, 1%–49% and <1%, camrelizumab + chemotherapy (HR 0.48, 95% CI: 0.21–1.11), cemiplimab + chemotherapy (HR 0.50, 95% CI: 0.32–0.79) and nivolumab + ipilimumab (HR 0.64, 95% CI: 0.51–0.81) were considered optimal treatments. Compared with chemotherapy, monotherapy with nivolumab, cemiplimab, pembrolizumab, atezolizumab and durvalumab had lower odds of TRAE grade ≥3.ConclusionIn all patients, penpulimab plus chemotherapy was the most effective therapy, but treatment preferences varied by PD-L1 expression, histology type and associated outcomes. Safety at the individual patient level must be a high priority in the decision-making process. Further validation is warranted.